FAKTOR – FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN PT KOBEXINDO TRACTORS Tbk CABANG SAMARINDA - Eka Yudhyani3, Muhammad Saripudin1, Theresia Militina2, (EKONOMIA, 2020)
Factors Affecting the Performance of Employees of PT Kobexindo Tractors Tbk Samarinda Branch" under the guidance of Mrs. Theresia Militina as Advisor Lecturer I and Ms. Eka Yudhyani as Supervisor II.The purpose of this study was to determine the effect of variables of leadership, compensation, motivation, and work discipline on the performance of employees of PT Kobexindo Tractors Tbk Samarinda Branch. According to Arikunto (2003: 112), this research is population research because all employees who work at PT Kobexindo Tractors Tbk Samarinda Branch are 35 people and because the population is small, saturated sampling or census techniques are used, which is the entire population as the research sample.        Leadership has a positive but not significant effect on the performance of employees of PT Kobexindo Tractors Tbk Samarinda Branch. The results of this study to explain that the leadership at PT Kobexindo Tractors Tbk Samarinda Branch has not run as expected. Compensation variables affect the performance of employees of PT Kobexindo Tractors Tbk Samarinda Branch. This is because there are positive and significant influences between the two variables. The results of this study want to explain that proper compensation is in accordance with the life needs of employees / employees of PT Kobexindo Tractors Tbk Samarinda. Motivation variable affects the performance of employees of PT Kobexindo Tractors Tbk Samarinda Branch. This is because there are positive and significant influences between the two variables. The results of this study want to explain that work motivation can increase work enthusiasm, so that it affects the performance of employees. Discipline variables affect the performance of employees of PT Kobexindo Tractors Tbk Samarinda Branch. This is because there are positive and significant influences between the two variables. The results of this study to explain that work discipline can improve employee performance.